2010
DOI: 10.22323/2.09030203
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic on the air: a case study on the coverage of new influenza A/H1N1 by Brazilian prime time TV news

Abstract: In this paper we analyze the coverage of the pandemic influenza caused by the A (H1N1) virus by the main Brazilian TV news. Jornal Nacional (JN) – which can be roughly translated with National News – reaches an average of 25 million people throughout the country daily. We have observed that the attention cycle given to the new flu by JN lasted approximately five months with significant space given to the disease. Most of the news highlighted the number of illness cases and the health measures to control the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…This general uncertainty concerning the necessity and possible side effects of the vaccine paired with a sensationalizing media coverage regarding the consequences of H1N1 can be observed in almost all affected countries. [10][11][12][13][14][15][16] Especially studies on the public's assessment of the media's performance during the pandemic find much criticism. The perception that the media played up the threat posed by the virus was a recurring element among this criticism: a qualitative study from New Zealand speaks of the media as over-hyping the risk.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…This general uncertainty concerning the necessity and possible side effects of the vaccine paired with a sensationalizing media coverage regarding the consequences of H1N1 can be observed in almost all affected countries. [10][11][12][13][14][15][16] Especially studies on the public's assessment of the media's performance during the pandemic find much criticism. The perception that the media played up the threat posed by the virus was a recurring element among this criticism: a qualitative study from New Zealand speaks of the media as over-hyping the risk.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…Indeed, the media have often been criticized for inadequate and inaccurate coverage . Studies have found that media coverage tends to overemphasize risks, as well as negative consequences and potential damages of risks, an observation that can be explained by the SARF.…”
Section: Media and Crisis Communicationmentioning
confidence: 99%
“…When direct experience with risks is lacking, information flow via the media is assumed to become the central agent of public risk perception and thus possibly amplification . SARF specifies four attributes that may influence amplifications in the flow of information: the volume of information, the degree of debates about risks, dramatization, and symbolic connotations .…”
Section: Sarfmentioning
confidence: 99%
“…66 But also a shift in emphasis to fears and panic in society rather than research and scientific development is feasible, as was observed in media reports about the new disease H1N1 in 2009 in Brazil. 67 Also such a shift results in an emphasis on news values (negativity, threat) that fit the modern media logic.…”
Section: Media Logicmentioning
confidence: 99%